Pengembangan Sistem Informasi Pendidikan (Simdik) Pada Lembaga Pendidikan Di Era Digital - Kuni Fatonah; Lailatu Udngiati (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
The rapid advancement of information technology in the digital era requires educational institutions to optimize data management and administration effectively and efficiently through the use of information systems. This study aims to analyze the development of the Educational Management Information System (SIMDIK) and examine its implementation and benefits in improving the quality of educational institution management. In this digital age, educational institutions are required to improve the quality of education by utilizing technological developments in various aspects, both academic and administrative processes, through the management information systems implemented by schools. The method used was a qualitative approach with a literature study sourced from various scientific journals, books, and relevant references. Data collection was conducted through the collection of various articles, while data analysis employed descriptive qualitative techniques through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that SIMDIK development generally uses a System Development Life Cycle (SDLC) approach, encompassing needs analysis, design, development, testing, implementation, and ongoing evaluation. SIMDIK consists of key components: hardware, software, databases, human resources, and integrated procedures. SIMDIK implementation has been proven to improve administrative efficiency, data accuracy, ease of access to information, and support data-driven decision-making. However, its development still faces various obstacles such as limited infrastructure, low digital literacy among human resources, relatively high costs, and data security issues. Therefore, ongoing support and innovative development are needed for SIMDIK's optimal implementation to improve the quality of education management in the digital era.